INFLUENCE OF PRODUCT PACKAGING, PROMOTIONS AND STORE ENVIRONMENT OF THE RETAIL INDUSTRY ON THE IMPULSIVE PURCHASING BEHAVIOUR OF FEMALES IN DHAKA, BANGLADESH - Islam, Mohd Hamza; Ahmad , Rohizan Binti; Dada , Morakinyo (Electronic Journal of Business and Management, 2022)
This study aims to critically understand the factors influencing the impulsive purchasing behaviour of females in Dhaka, Bangladesh. The research examines three independent variables: product packaging, promotional approaches, and store environment. Primary data was collected through questionnaires and verified using the Cronbach’s Alpha reliability test. The findings reveal a significant relationship between all variables and impulsive purchasing. Specifically, promotions were found to have the highest influence, followed by product packaging, and finally the store environment. The study suggests that retail sectors in Dhaka can improve sales by strategically targeting these factors, especially among female customers who dominate the retail market.